Editorial: what is normal function of a pelvic pouch? Authors' reply. Issue 11 (10th May 2022) - Quinn, Kevin P.; Busciglio, Irene A.; Burton, Duane D.; Inoue, Akitoshi; Lee, Yong S.; Heiken, Jay P.; Sheedy, Shannon P.; Fletcher, Joel G.; Raffals, Laura E.
LINKED CONTENT: This article is linked to Quinn et al papers. To view these articles, visit https://doi.org/10.1111/apt.16859 and https://doi.org/10.1111/apt.16916